2018
DOI: 10.1177/0890334418817516
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Breastfeeding Exposure, Knowledge, and Attitudes in Collegiate Males Residing in East Texas

Abstract: Background: Researchers exploring breastfeeding attitudes and knowledge among women suggest the decision to breastfeed is influenced by the male partner, yet few studies address males. Because collegiate males will soon enter fatherhood, assessment of their attitudes and knowledge may inform interventions aimed at increasing intention to breastfeed. Research aim: This study aimed to describe collegiate males’ exposure to, attitude toward, and knowledge about breastfeeding. Methods: A cross-sectional online sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…An exploratory factor analysis of the scale indicated it to be a valid measure of breastfeeding knowledge and understanding among this sample of adult college students but was not found to be reliable when tested a second time in a subset of study participants. The author of the current study agrees with the suggestions of investigators of similar breastfeeding knowledge studies, conducted previously among college students in the US, to increase the diversity of samples and to expand participant recruitment to include a represent able sample of adult college students nationwide (Heathman et al, 2019;Kavanagh et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…An exploratory factor analysis of the scale indicated it to be a valid measure of breastfeeding knowledge and understanding among this sample of adult college students but was not found to be reliable when tested a second time in a subset of study participants. The author of the current study agrees with the suggestions of investigators of similar breastfeeding knowledge studies, conducted previously among college students in the US, to increase the diversity of samples and to expand participant recruitment to include a represent able sample of adult college students nationwide (Heathman et al, 2019;Kavanagh et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…These results are similar to other studies that assessed breastfeeding knowledge in some way among adult college students with regard to higher scores among those of older age (Hamade et al, 2014;Lou et al, 2014), female (Chang et al, 2012;Kavanagh et al, 2012;Payghan & Kadam, 2012), married (Ebrahim et al, 2011), being born in the US (Chang et al, 2012), and Caucasian race (Jefferson, 2017) in the samples. Two previous studies had found no difference in breastfeeding knowledge by race (Chang et al, 2012;Heathman et al, 2019). There were also conflicting results regarding significant differences in score among students were breastfed as children or not.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation